Building Resilience in a Child of Divorce: A Single-Case Study on Positive Psychological Interventions - Mariyani, Devi; Ayriza, Yulia; Harmiati, Harmiati; Sahin, Arif (Indonesian Journal Publisher, 2025)
This study aimed to examine the effectiveness of positive psychological interventions in enhancing resilience among children of divorced parents in a rural, low-education context. A qualitative case study was conducted with a 13-year-old male participant from North Bengkulu, Indonesia, who had experienced parental divorce since early childhood. Data were collected through in-depth interviews, observation, and documentation. The interventions included gratitude journaling, hope building, positive self-affirmation, and enhancement of social relationships. Findings demonstrated improvements in resilience across four domains: (1) emotional regulation, shifting from destructive to adaptive emotional expression; (2) optimism, moving from pessimism toward setting small academic goals; (3) self-efficacy, progressing from negative self-image to increased confidence through positive affirmation; and (4) social relationships, developing from social withdrawal to active peer engagement. These results indicate that positive psychological interventions are effective in strengthening resilience in children from divorced families. The study contributes to filling a gap in research on the application of positive psychology for children of divorced parents in rural areas, with implications for designing culturally sensitive psychological support programs.